Exploring Expressive Language Disorders in Children with Autism in Banyuwangi: A Psycholinguistic Review - Akhmad Sofyan; Muta’allim; Saepulloh; Asia Anis Sulalah; Sahrotul Qeisiyeh (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Autism is a complex neurodevelopmental disorder that affects various aspects of a child's development, including language abilities. This study aims to identify and analyze the fluency, articulation, and sentence structure abilities of autistic children at SMAN 1 Glenmore, Banyuwangi Regency. The research employs a qualitative descriptive design. The data in this study consists of words and sentences, with the data sources being autistic students from Class X IPS4 at SMAN 1 Glenmore Banyuwangi. The method used for data collection is the observation-participation method, where the researcher observes the spoken and written expressions of autistic students from Class X IPS4 SMAN 1 Glenmore Banyuwangi through recording and note-taking techniques. Additionally, interviews were conducted with the autistic students, teachers, parents, and the students' peers. After the data was collected, the researcher performed data reduction, classification, verification, tabulation, and coding for each data set. Finally, the researcher interpreted the data and drew conclusions. The results of the study indicate that the expressive language abilities of autistic children are still hindered by several factors, such as fluency in speaking, pronunciation, and unclear articulation, especially in words containing the letters or endings L, N, M, R, T, and NG. Autistic children tend to speak in short phrases and are experience significant challenges in active communication, nor can they convey information clearly. However, Bela Citra Kinanjur (BCK) is able to write independently with simple compositions, although some grammatical errors are still present, such as in the use of articles, spacing, and writing mechanics. Based on these findings, it is recommended that teachers help build the confidence of autistic students through public speaking activities, writing therapy, and word-building stimulation.